PENGARUH TIPE INDUSTRI, VISIBILITAS PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN EMISI KARBON (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Irine Tessa Koeswandini; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2019)
This study aimed to obtain empirical evidence about the influence of type of industry, profitability, company’s size, and company’s leverage to the extent of emission carbon disclosure in Indonesia companies. To measure the extent of carbon emission disclosure used checklist that was developed based on the information request sheets provided by the carbon disclosure project (CDP). The population of this study was all companies listed in Indonesia Stock Exchange (IDX) in 2015-2017. Sample of this study was non financial companies listed in Indonesia Stock Exchange (IDX) in 2015-2017 used purposive sampling method. There were 19 companies in 2015, 19 companies in 2016, 19 companies in 2017 which fulfilled criterion as the research sample. The classical assumpstion was used for data analysis and regression analysis for testing hypothesis. The results of this study showed that firm size and companies’ Leverage significantly influence to the extent of carbon emission disclosure. Meanwhile type of industry and profitability had no significantly influence to to the extent of carbon emission disclosure.